2019
DOI: 10.3390/md17050275
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Existence of Quorum Sensing Inhibitors in Marine Bacteria: Potential Drugs to Combat Pathogens with Novel Strategies

Abstract: Quorum sensing (QS) is a phenomenon of intercellular communication discovered mainly in bacteria. A QS system consisting of QS signal molecules and regulatory protein components could control physiological behaviors and virulence gene expression of bacterial pathogens. Therefore, QS inhibition could be a novel strategy to combat pathogens and related diseases. QS inhibitors (QSIs), mainly categorized into small chemical molecules and quorum quenching enzymes, could be extracted from diverse sources in marine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 102 publications
(121 reference statements)
0
24
0
Order By: Relevance
“…However, because of the adverse impacts of chemicals on the environment and human health, they are no longer recommended for use [ 7 , 8 ]. Therefore, quorum quenching (QQ) based on the disruption of quorum sensing (QS) has been put forward and regarded as a promising strategy to combat pathogenic infection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the adverse impacts of chemicals on the environment and human health, they are no longer recommended for use [ 7 , 8 ]. Therefore, quorum quenching (QQ) based on the disruption of quorum sensing (QS) has been put forward and regarded as a promising strategy to combat pathogenic infection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural antimicrobials are known to be effective in reducing bacterial pathogenicity via direct [13] or indirect [26] anti-virulence activity. For example, the surface proteins involved in the virulence of Staphylococcus aureus are inhibited by venom peptides from being promising candidates for the treatment of related infections caused by multi-drug resistant bacteria [27] Quorum-sensing molecules originating from marine bacteria can control virulence, with gene expression being described as a novel antimicrobial strategy in aquaculture [28]. Another mechanism by which natural antimicrobials can reduce virulence refers to their involvement in bacterial physiology, as it has been shown that phenolic compounds can disrupt the expression and function of efflux pumps [29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prokaryotic byproducts is one of the strategies popularly adopted to interrupt QS mechanism. Numerous reports on bacterial metabolites with QQ activity have been published, including those from marine sources (some examples will be presented later in this review [18,22,66,67,68]. However, information on marine microbial species is limited when compared to their terrestrial counterparts, and many molecules remain to be identified [66].…”
Section: Quorum Sensing Inhibitorsmentioning
confidence: 99%